IUTAM Symposium on Size Effects on Material and Structural Behavior at Micron- and Nano-Scales Proceedings of the IUTAM Symposium held in Hong Kong, China, 31 May - 4 June, 2004 - Sun, Q. P.; Tong, P. (Solid Mechanics and Its Applications,, 2006)
Size effects on material and structural behaviors are of great interest to physicists, material scientists, and engineers who need to understand and model the mechanical behavior of solids especially at micron- and nano-scales. This volume is a collection of twenty five written contributions by distinguished invited speakers from seven countries to the IUTAM Symposium on Size Effects on Material and Structural Behavior at Micron- and Nano-scales. It contains basic theoretical and experimental aspects of the recent advances in the mechanics research of various size effects. Main topics include: behaviors of materials and structures at micron- and nanometer-scales; physical bases of size effects; adaptive and multi-functional behaviors of materials at small scales; size effects in fracture and phase transformation of solids; multi-scale modeling and simulation; size effects in material instability and its propagation, etc. Due to the multidisciplinary nature of the research covered, this volume will be of interest to engineers, scientists, researchers, and graduate students in the field of theoretical and applied mechanics, materials science as well as technology.